Pengaruh kolonialisme Jepang terhadap pendidikan Islam - Saifudin, Saifudin; Saepuddin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2020)
This article discusses the impact of Japanese colonialism on Islamic education, namely on how Islamic education was held during the Japanese period. The writing of this research is qualitative research. The methodology and approach used are historical analysis and content analysis. The main source of research is books on the history of Islamic education written by actors of the history of Japanese colonialism and other relevant books. This article concludes that Japanese colonialism has influenced the system, goals, form, appearance and curriculum of Islamic education. This influence did not only occur during the Japanese colonialism or occupation, but also continues to this day. The influence of Japanese colonialism on Islamic education, among other things, changed the aim of Islamic education from fulfilling the happiness of the world and the hereafter to the fulfillment of worldly needs only. The spiritual aspect (hereafter) is considered unimportant and needed in education, because it is considered to not affect increasing one's happiness in the world. Abstrak Artikel ini membahas dampak penjajahan Jepang atas Pendidikan Islam yaitu mengenai bagaimana pendidikan Islam diselenggarakan pada masa Jepang. Penulisan penelitian ini merupakan penelitian kualitatif. Metodologi dan pendekatan yang digunakan adalah analisis historis dan analisis isi (content analysis). Sumber utama penelitian buku-buku sejarah pendidikan Islam yang ditulis para pelaku sejarah penjajahan Jepang dan buku-buku lain yang relevan. Artikel ini menyimpulkan bahwa kolonialisme Jepang telah memengaruhi sistem, tujuan, bentuk, rupa, dan kurikulum pendidikan Islam. Pengaruh tersebut tidak hanya terjadi pada masa kolonialisme atau penjajahan Jepang, tetapi juga berlangsung hingga hari ini. Pengaruh kolonialisme Jepang atas pendidikan Islam, antara lain, mengubah tujuan pendidikan Islam dari tujuan pemenuhan kebahagiaan dunia dan akhirat diubah menjadi pemenuhan kebutuhan duniawi semata yang bersifat jasadi. Adapun aspek rohani (akhirat) dianggap tidak penting dan dibutuhkan dalam pendidikan, karena dianggap tidak berpengaruh pada peningkatan kebahagiaan hidup seseorang di dunia.